Restoring road performance of recycled asphalt mastic through filler asphalt ratio adjustment - Yu Cai; Linhui Cao; Jue Guo; Zhifei Tan (Scientific Reports)
Abstract The integration of reclaimed asphalt pavement (RAP) in road construction offers substantial environmental and economic benefits, yet the performance degradation of recycled asphalt mixtures due to binder aging remains a critical challenge. This study addresses this issue by proposing a novel filler-to-asphalt (F/A) ratio optimization strategy for recycled asphalt mastic containing 50% aged binder. Recycled mastics with F/A ratios spanning 0.0 (pure binder control) to 1.5 were evaluated using dynamic shear rheometer (DSR) and bending beam rheometer (BBR) to assess rutting resistance, fatigue life, and low-temperature cracking performance. Results demonstrate that mineral filler amplifies the stiffening effects of aged binder, improving high-temperature stability but exacerbating low-temperature brittleness. Fatigue performance exhibited method-dependent behavior, with time sweep tests indicating extended fatigue life but fatigue factor analysis revealing accelerated damage accumulation. Additionally, strong exponential or linear relationships were established between performance indicators and the F/A ratio. Based on these relationships, an F/A ratio adjustment value of 0.3 to 0.5 was identified to achieve performance comparable to that of virgin asphalt mastic. These findings provide a viable approach for optimizing the mix design of recycled asphalt mixtures containing RAP.